Chronology, Narrative, and Founding Acts: Between a Transcendental Rock and a Decisionist Hard Place - Jack Reilly ([sic])
In attempting to represent political transformations, we often encounter a moment that seems to resist narrativisation, a moment of obstinate inconsistency which various theoretical, historical and fictional accounts cannot properly absorb except by way of indicating the parameters of a rupture. Here, I present a position which views these unrepresentable moments as structurally necessary features of revolutionary events. It is not simply that, at such historical junctures, we are faced with an abundance of information and that the unrepresentability or narrative deficit is the consequence of this surplus; on the contrary, the founding act that accompanies any radical transformation necessarily involves a certain temporal contraction. To the extent that narrative relies on a linear chronology, it fails to capture this moment of contraction. Indeed, this is why works of political philosophy associated with a founding contract (for example Hobbes’s Leviathan and Rousseau’s Social Contract) cannot fully suppress the moment of circularity in which the rhythm of chronological time skips a beat and, to paraphrase Rousseau, one requires an effect to perform the function associated with its own cause. If the moment of founding can be represented at all, it is only by way of paradox and metaphor.